(untitled) (Annals of Bangladesh Agriculture, 2020)
The breeding season of fishes plays an important role in fish domestication and conservation of fish diversity. Freshwater goby, Glossogobius giuris is an important food fish of Bangladesh. Therefore, a study was performed to determine the breeding biology through assessing the gonadosomatic index (IG), fecundity and histology of gonad of G. giuris. A total of 1371 females and 1051 male fishes were collected from the Belai beel of Gazipur district. Significantly (P<0.05) higher values of mean IG were observed during March and from June to August for both females and males. The highest mean fecundity was recorded in August and the lowest was recorded in May. The smallest mean oocyte length was 0.037±0.005 mm in May and the largest was 0.071±0.001 mm in August. The early and late perinucleolar stages of oocytes were observed from January to March. The yolk vesicle stage was observed during April to May and yolk granule stage was observed during March and from June to August. These results revealed that G. giuris might breed in March and from June to August. Ann. Bangladesh Agric. (2019) 23(1) : 1-13